Effects of Physical Activity and Training Routine on Mental Health During the COVID-19 Pandemic and Curfew - Sokić, Jelena; Popov, Stanislava; Dinić, Bojana M.; Rastović, Jovana (Frontiers in Psychology, 2021)
This research aimed to explore the effects of physical activity and training routine on mental health during the COVID-19 pandemic and the proclaimed emergency state and curfew. To measure the mental health components of psychological distress and subjective well-being, two studies were conducted on different samples: Study 1 during the beginning of curfew in Serbia (N = 678) and Study 2 during the ending phase (N = 398). The results of Study 1 showed that elite athletes as well as those with high level of physical activity experienced the lowest distress. Furthermore, effects of the changes in the training routine on distress among physically active individuals depended on the level of sports participation with elite athletes who reduced trainings showing lower anxiety compared to recreational athletes who reduced trainings as well or kept the same training routine. Thus, we could conclude that in the early stage of the pandemic, elite athletes showed better mental health and adaptability to the crisis situation. Results of Study 2 showed that although all the participants had decreased well-being during the curfew, compared to the period before the pandemic and the curfew, there were no differences in well-being between elite and recreational athletes, who had higher well-being compared to non-athletes. However, this effect held both before and during the curfew showing that physically active individuals did not additionally benefit from this decrease compared to the non-active. Furthermore, athletes who became physically inactive showed lower well-being compared to those who kept the same training routine. Thus, in the later stage of the pandemic, prolonged physical inactivity had negative effects on mental health.